Beam-Column Element for Nonlinear Seismic Analysis of Steel Frames - Kim, Kee Dong; Engelhardt, Michael D (Journal of structural engineering (New York, N.Y.), 2000)
This paper describes a beam-column element intended to model steel members with flexural yielding, as well as members with yielding under combined flexure and axial force in frames subject to earthquake ground motions. The element has the capability to model plastic axial deformation and changes in axial stiffness, and it employs hardening rules to handle monotonic, cyclic, or arbitrary loading. When compared with experimental results and fiber model predictions, the element shows significantly better performance than typical bilinear hinge models. The developed element can more accurately predict local deformation demands and the overall response of structural systems under earthquake loading than the bilinear hinge element.